Dendritic cells and γδ T cells interaction during infections (Hematology Meeting Reports, 2009)
T-cell derived signals combined to innate stimuli promote the activation of dendritic cells (DC) and regulate the adaptive immune response.1 Understanding these signals is crucial to manipulate the immune system for new vaccination strategies and especially for infectious diseases. Both CD4+ and CD8+ T-cells have been involved in the activation of DCs2 but the pool of antigen-specific βα T-cells available to provide such signals at the site of infections would likely be small.